Aid and donor countries' GNP - Hans W. Singer; Mohinder L. Puri (Intereconomics, 1974)
The authors try to test statistically whether the flow of resources between poor and rich countries has in fact conformed to the “1 per cent” target defined by the United Nations. Basis for testing several hypotheses are data published by the Development Assistance Committee (DAC) of the OECD.
Keywords: 330; Development Aid